Individual characteristics, institutional incentives and electoral abstention in western Europe - Anduiza Perea, Eva (2003)
This article examines the interaction between individual characteristics and institutional incentives over non-voting, with a special focus on the interaction between these two types of explanatory variables. The analysis of survey and contextual data regarding parliamentary elections in 15 western European countries shows that the effect of individual resources and motivations on abstention is not constant across different countries. Conversely, the effect of institutional incentives (compulsory voting, voting facilities, electoral thresholds of representation and preference expression) over non-voting depends on the elector's level of resources and motivations. One of the four institutional incentives considered has even opposite effects for citizens with different individual characteristics. The analysis also shows that when analysing interactions it is fundamental to distinguish between magnitudes and consequences of the effects of explanatory variables. This has important implications for the interpretation of the results of logistic regression analysis.